Microplastics Contamination in Breast Milk and Infant Milk Products in Indonesia - Sincihu, Yudhiakuari; Susetio, Mercy Mezia; Tang, Michelle; Julian, Alvin; Sudewi, Ni Putu; Lestari, Kusuma Scorpia; Ningrum, Prehatin Trirahayu (Gema Lingkungan Kesehatan, 2025)
Microplastics contamination has been detected in milk consumed by infants, with estimates suggesting an intake of 106-113 microplastic particles per day. These particles may pose potential health risks. However, the microplastic contamination in breast milk and formula milk in Indonesia remain unclear. This study aims to address this gap. This study employed a descriptive observational design with a cross-sectional approach. Microplastic detection was carried out on four groups: fresh breast milk, breast milk stored in plastic bags, powdered formula milk, and liquid formula milk. Breast milk samples were collected from breastfeeding mothers at Puskesmas Mulyorejo, while formula milk was obtained from various market in Surabaya. The processed samples were filtered using filter paper, and the retained particles were examined. The number and shape of microplastic particles were identified using a binocular microscope, while the polymer characteristics were analyzed using micro-FTIR. The average number of microplastic particles was highest in powdered formula milk (15.34±4.74), followed by liquid formula milk (11.59±9.50), stored breast milk (6.07±5.46), and fresh breast milk (1.41±1.50). Microplastic contamination was not detected in 17 out of 46 breast milk samples. Fragmented microplastic particle shapes dominated all samples. Nylon and Polymethyl Methacrylate were the most common plastic polymers in breast milk, while Polyoxymethylene, Polyvinyl Chloride, and Polymethylpentene were prevalent in formula milk. In conclusion, microplastic contamination in breast milk was minimal compared to formula milk, making breast milk the best feeding option for infants.